Unplanned pregnancy and the association with maternal health and pregnancy outcomes: A Swedish cohort study. - Alisa Carlander; Jenny Niemeyer Hultstrand; Isa Reuterwall; Maria Jonsson; Tanja Tydén; Merit Kullinger (PLoS ONE, 2023)
Objectives Unplanned pregnancies are common and associated with late initiation and inadequate antenatal care attendance, which may pose health risks to mother and child. How pregnancy planning relates to maternal health and delivery in Sweden, a country with free antenatal care and free abortion, has not been studied previously. Our aims were to study whether pregnancy planning was associated with antenatal care utilization and pregnancy outcomes in a Swedish setting. Methods Data for 2953 women, who answered a questionnaire when recruited at antenatal clinics in Sweden and later gave birth, was linked to the Swedish Medical Birth Register. The degree of pregnancy planning was estimated using the London Measure of Unplanned Pregnancy. Unplanned (comprising unplanned and ambivalent intention to pregnancy) was compared to planned pregnancy. Differences between women with unplanned and planned pregnancy intention and associated pregnancy outcomes were analyzed using Fisher's exact test and logistic regression. Results There were 31% unplanned (2% unplanned and 29% ambivalent) pregnancies, whereas most woman (69%) reported their pregnancy to be planned. Women with an unplanned pregnancy enrolled later to antenatal care, but there was no difference in number of visits compared with planned pregnancy. Women with an unplanned pregnancy had higher odds to have induced labor (17% versus 13%; aOR 1.33 95% CI 1.06-1.67) and a longer hospital stay (41% versus 37%; aOR 1.21 95% CI 1.02-1.44). No associations were found between pregnancy planning and pregnancy-induced hypertension, gestational diabetes mellitus, preeclampsia, epidural analgesia use, vacuum extraction delivery, Caesarean section or sphincter rupture. Conclusions Unplanned pregnancy was associated with delayed initiation of antenatal care, higher odds for induction of labor and longer hospital stay, but not with any severe pregnancy outcomes. These findings suggest that women with an unplanned pregnancy cope well in a setting with free abortion and free health care.